Green Awareness and Eco-Friendly Products Shaping Purchase Decisions through Moral Obligation and Social Influence - Sudadi Pranata; Dewi Laily Purnamasari; Oryz Agnu Dian Wulandari (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine how environmental awareness and the availability of eco-friendly products influence purchase decisions in Small and Medium Enterprises (SMEs) that sell eco-friendly food. Research Methodology: This study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through a survey of consumers who had previously purchased eco-friendly food products, and the proposed relationships were analyzed using Smart-PLS. Results: The findings revealed that environmental awareness did not directly influence purchase decisions. However, it significantly affected purchase decisions indirectly through social influence, indicating a full mediating effect. In contrast, eco-friendly product availability had a significant direct effect on purchase decisions and an additional indirect effect through moral obligation, demonstrating the complementary role of moral motivation in sustainable consumption behavior. Conclusions: Sustainable purchasing behavior is shaped more strongly by social influence and moral obligation than environmental awareness alone. The results emphasize the importance of integrating social and ethical mechanisms into strategies that promote eco-friendly consumption. Limitations: This study is limited by its cross-sectional design and reliance on self-reported responses from consumers of urban eco-friendly food SMEs. Contributions: This study extends the Norm Activation Model by explicitly demonstrating the mediating roles of social influence and moral obligation in sustainable purchasing decisions. These findings provide practical insights for food SMEs and green marketing practitioners seeking to strengthen consumer engagement with eco-friendly products.